2014
DOI: 10.1093/cercor/bhu065
|View full text |Cite
|
Sign up to set email alerts
|

The Corticospinal Tract in Huntington's Disease

Abstract: Huntington's disease (HD) is characterized by progressive motor impairment. Therefore, the connectivity of the corticospinal tract (CST), which is the main white matter (WM) pathway that conducts motor impulses from the primary motor cortex to the spinal cord, merits particular attention. WM abnormalities have already been shown in presymptomatic (Pre-HD) and symptomatic HD subjects using magnetic resonance imaging (MRI). In the present study, we examined CST microstructure using diffusion tensor imaging (DTI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 119 publications
5
28
0
Order By: Relevance
“…Previous DTI studies have demonstrated white matter deficits in the corpus callosum [Crawford et al, 2013], internal capsule [Rosas et al, 2006], corticospinal tract [Phillips et al, 2015], cortico-striatal circuit [Novak et al, 2014], and across extensively distributed white matter fibers [Novak et al, 2014;Reading et al, 2005], years before symptoms occur. In addition to the existing findings, our data provide a more comprehensive spatial and temporal view of the changing pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Previous DTI studies have demonstrated white matter deficits in the corpus callosum [Crawford et al, 2013], internal capsule [Rosas et al, 2006], corticospinal tract [Phillips et al, 2015], cortico-striatal circuit [Novak et al, 2014], and across extensively distributed white matter fibers [Novak et al, 2014;Reading et al, 2005], years before symptoms occur. In addition to the existing findings, our data provide a more comprehensive spatial and temporal view of the changing pattern.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, diffuse increases in corticospinal FA are observed throughout childhood and adolescence as part of normal neural development [49; 60]. Reduced corticospinal FA, on the other hand, is common in diseases associated with loss of motor and executive function, including Huntington’s disease [47], multiple sclerosis [32], cerebral palsy in children [48], multiple system atrophy [33], and amyotrophic lateral sclerosis [9]. In contrast, increased corticospinal FA is observed with recovery of motor function following diffuse axonal injury [31], and more commonly with motor learning.…”
Section: Discussionmentioning
confidence: 99%
“…T2* weighted volumes, which are sensitive to iron/ferritin [21] , [22] are useful to investigate the iron content that is associated with the remyelination process [2] . The few studies present in literature show a non-univocal picture of the regional white matter iron content changes in HD, with no iron level differences in the callosal splenium, but decreased iron levels in the frontal lobe white matter [2] , the callosal isthmus [14] and the cortical spinal white matter tract [15] . However, no studies to date in HD have combined the sensitivity of DTI tractography to identify the deep white matter in-vivo with T2* weighted volume images.…”
Section: Introductionmentioning
confidence: 93%
“…Changes in iron content (reduction) manifest in the early stages of HD, likely indicating a failure of the remyelination processes at that time. Then we focused on the cortical spinal tract, which is the brain's main motor fiber [15] . We found that a likely active repair mechanism (as indicated by increased iron) helps keep the cortical spinal tract at a normal functional level in the presymptomatic stage.…”
Section: Introductionmentioning
confidence: 99%